Satisfação no trabalho e sintomas osteomusculares em costureiras autônomas e empregadas da região metropolitana de Goiânia - Casa Junior, Adroaldo José (2018)
Thesis written using scientific article style. The first article, submitted to “Revista de Saúde Pública” and entitled “Investigation of musculoskeletal symptoms of seamstresses in the metropolitan region of Goiânia (Goiás)”, comprised a cross-sectional, analytical and quantitative study. The goal was to evaluate and compare musculoskeletal symptoms in 417 seamstresses, either self-employed or factory-employed. The Identification and Assessment Survey was employed to obtain socio-demographic and labor-related data, and The Nordic Musculoskeletal Questionnaire to evaluate physical symptoms present in the previous 12 months. A high prevalence of musculoskeletal symptoms was observed, mainly in the dorsal, lumbar and cervical regions, as well as in the shoulders and wrists/hands/fingers. Pain, numbness, and tingling was more prevalent in self-employed workers (<0,001) and among those who had been in the profession >10 years (p=0,04). Most workers indicated they had some type of medical and/or physical therapy intervention to treat musculoskeletal symptoms during the 12-month period (p=0,01). The second article, submitted to “Ciência & Saúde Coletiva” and entitled “Work life quality analysis of seamstresses in the metropolitan region of Goiânia (Goiás)”, was a cross-sectional and analytical study, where the objective was to evaluate and compare the quality of work life of self-employed and factory-employed seamstresses from Goiás state in Brazil. A Quality of Work Life Questionnaire-bref (QWLQ-bref) was used to evaluate the physical/health, personal, professional and psychological status of each worker. The total points average was 3,3 (±0,3) or 55,1%, indicating satisfactory work life quality. Looking at each component separately, the physical/health aspect was considered satisfactory; whereas psychological, personal and professional aspects were considered neutral. In the comparison of self-employed and factory-employed seamstresses, compared to the averages obtained in the 4 domains, we observed a significant difference only in the physical/health aspect (p=0,02), with a significantly higher score among the self-employed. No significant difference was observed in the general frequencies between seamstresses self-employed and factory-employed in the answers given to the 20 QWLQ-bref questions.